LEGAL CONSEQUENCES OF PRENUPTIAL AGREEMENTS FROM THE PERSPECTIVE OF NATIONAL LAW - A.A. Ngurah Bagus Rajendra; I Gusti Ngurah Dharma Laksana (Transpublika Publisher, 2024)
This study aims to assess the importance of prenuptial agreements for Indonesian citizens marrying either fellow Indonesian citizens or foreign citizens, as well as to evaluate the legal framework provided by Law no. 1 of 1974 and Decision Number 69 / PUU-XIII / 2015 concerning marriages involving Indonesian citizens and foreign citizens. The research methodology utilized in this study is normative legal research, with data collection primarily based on a literature review. The results of this study highlight the significance of prenuptial agreements for Indonesian citizens, as they can act as a form of protection in the event of unexpected circumstances such as divorce. As per the legal regulations outlined in Law no. 1 of 1974 and Decision Number 69 / PUU-XIII / 2015, prenuptial agreements must be documented in writing and properly authenticated by the Marriage Registrar. It is crucial that the terms of the agreement adhere to legal, religious, and ethical standards.